Effect of Frequent Use of Ovulation Stimulants drugs on, Total Cholesterol, Triglycerides, High density lipoprotein and Total Antioxidants - Humaidan, Rana; Al-Azzawi, Buthainah (Journal of Biomedicine and Biochemistry, 2024)
Background Letrozole, an aromatase inhibitor, inhibits the final stage of conversion of androgens into estrogens, affecting organs and tissues such as the ovaries, breasts, adipose tissue, and bone. This mechanism greatly reduces the effects of estrogen. Estrogens are important for controlling the metabolism of fats and lipoproteins, influencing total protein, total antioxidants, and total cholesterol. FSH stimulation can benefit patients with pituitary dysfunction and is used to promote ovulation in women who have not become pregnant. It also provides controlled stimulation of ovarian hyperstimulation, which increases the number of follicles in in vitro fertilization.The Aim To assess the difference in the level (total cholesterol, Triglyc- erides, High density lipoprotein and total antioxidants) of infertility treat- ment among the three study groups, the group that injected by FSH, the group that took Letrozole, and the control group.Material and Method A study was conducted between October 2022 and May 2023. It involved one hundred and twenty patients, divided into three groups: those who took Letrozole continuously for more than one month, those who were injected by FSH continuously for more than one month, and the control group who did not take any drugs to induce ovu- lation.Results The results of this study showed an increase in the total an- tioxidant levels and total protein capacity levels in FSH compared to the other LET groups and the control group. Our study showed a significant difference (p value < 0.0001) in cholesterol concentrations, and total an- tioxidant capacity, compared to all studied groups, and an increase in total cholesterol levels was observed, as there was a significant difference (p value = 0.0012) in comparison to all studied groups.